Study the Performance of Duckweed and Effective Microbes in Removing Arsenic from the Soil of Paddy Field and Reducing Arsenic in Paddy - Chin, Sze Jing (2015)
Paddy is a source of carbohydrate for human consumption and statistically, more than 90% of Asian consumes rice. The more the intake of rice, more arsenic that are present in the soil are absorbed by the paddy. Arsenic is a metal that is harmful to the human health which is why phytoremediation plant (duckweed) and effective microbes were used in this research to reduce to the arsenic concentration in paddy soil and paddy grain. Duckweed is able to absorb arsenic from the contaminated soil. The results show that the concentration of arsenic in soil will affect the concentration of arsenic in duckweed and also the reproduction rate of duckweed. Besides that, duckweed and effective microbes have the ability to decrease the arsenic concentration in paddy plant, but the method which is using the mixture of effective microbes and duckweed in reducing the arsenic in paddy had the least potential in reducing the arsenic concentration in paddy.